India-EU relations in health services: prospects and challenges - Chanda, Rupa (BioMed Central, 2011)
BACKGROUND: India and the EU are currently negotiating a Trade and Investment Agreement which also covers services. This paper examines the opportunities for and constraints to India-EU relations in health services in the context of this agreement, focusing on the EU as a market for India's health services exports and collaboration. The paper provides an overview of key features of health services in the EU and India and their bearing on bilateral relations in this sector. METHODS: Twenty six semi-structured, in-person, and telephonic interviews were conducted in 2007-2008 in four Indian cities. The respondents included management and practitioners in a variety of healthcare establishments, health sector representatives in Indian industry associations, health sector officials in the Indian government, and official representatives of selected EU countries and the European Commission based in New Delhi. Secondary sources were used to supplement and corroborate these findings. RESULTS: The interviews revealed that India-EU relations in health services are currently very limited. However, several opportunity segments exist, namely: (i) Telemedicine; (ii) Clinical trials and research in India for EU-based pharmaceutical companies; (iii) Medical transcriptions and back office support; (iv) Medical value travel; and (v) Collaborative ventures in medical education, research, training, staff deployment, and product development. However, various factors constrain India's exports to the EU. These include data protection regulations; recognition requirements; insurance portability restrictions; discriminatory conditions; and cultural, social, and perception-related barriers. The interviews also revealed several constraints in the Indian health care sector, including disparity in domestic standards and training, absence of clear guidelines and procedures, and inadequate infrastructure. CONCLUSIONS: The paper concludes that although there are several promising areas for India-EU relations in health services, it will be difficult to realize these opportunities given the pre-dominance of public healthcare delivery in the EU and sensitivities associated with commercializing healthcare. Hence, a gradual approach based on pilot initiatives and selective collaboration would be advisable initially, which could be expanded once there is demonstrated evidence on outcomes. Overall, the paper makes a contribution to the social science and health literature by adding to the limited primary evidence base on globalization and health, especially from a developing-developed country and regional perspective.